Mortality From Alcohol-Related Liver Cirrhosis in Mexico (2000–2017) - Yeverino-Gutiérrez, Myrna L.; González-González, María del R.; González-Santiago, Omar (Frontiers in Public Health, 2020)
Background: Alcohol is the main cause of liver cirrhosis. The objective of this study was to analyze the mortality rates of alcohol-related cirrhosis in Mexico from 2000 to 2017. Methods: Mortality data from alcohol-related cirrhosis were obtained from the National Institute of Statistics and Geography. Rates were adjusted to the World Standard Population and were calculated with a direct method. The differences between genders were evaluated with Student's t-test, while the ANOVA test was used for differences among age groups. A trend analysis was performed with an ln regression of adjusted mortality rates and analyzed with Student's t-test. Results: The mean age-adjusted mortality rate during the study period was 13.28 per 100,000 inhabitants. A significant decrease in mortality rates was observed, from 20.55 to 10.62 per 100,000 inhabitants. All age groups studied showed a significant decrease in mortality. The mortality rate was higher in males than in females. Conclusions: Mortality from alcohol-related cirrhosis decreased in Mexico. Males still have the highest mortality rate.